International Health Regulations (2005) facilitate communication for in-flight contacts of a Middle East respiratory syndrome case, Hong Kong Special Administrative Region, 2014 - Poon Kwok-ming; Wong Miu-ling; Leung Yiu-hong; Sin Ka-wai; To May-kei Liza; Chuang Shuk-kwan (World Health Organization Regional Office for the Western Pacific, 2015)
The International Health Regulations (IHR) (2005) require World Health Organization Member States to notify events fulfilling two of four criteria: (1) serious public health impact; (2) unusual or unexpected event; (3) significant risk of international spread; or (4) significant risk of international travel or trade restrictions.1 In-flight transmission of infections like severe acute respiratory syndrome is well documented.2 With the enormous amount of air travel today, the risk of increasing in-flight transmission and subsequent international spread of infections are increasing. Prompt notification and information sharing under the IHR mechanism is critical for effective contact tracing and prompt control measures. We report on a case of in-flight exposure to an infection with significant public health risks that was successfully resolved using IHR (2005) guidelines.